Deposição de serrapilheira e ciclagem de nutrientes em Pinus taeda L. em sistema silvipastoril - Vargas, Filipe Marcel da Rosa (2011)
This work aimed to study the cycling of nutrients via litterfall in Pinus taeda in silvopastoral system, by quantifying the contribution of litter, the decomposition rate and this the return of nutrients (N, P, K, Ca and Mg ) as a function of spacing and sampling position. The deposition of litter in conventional forest planting density is higher than at low planting densities, used in integrated production systems. Although the deposition unit is smaller, the greater the density of planting. The period of the year in which there was greater deposition of leaf litter was the month of April, with the exception of the plant row at a density of 1,111 trees ha-1, which was in May. There was an interaction between plant density, distance from the plant line and time for the release of all macronutrients in the system, as well as for the C / N.